SERVICE TO STUDENTS WITH CULTURAL DIVERSITY, SOCIO ECONOMIC, INTELLIGENCE AND LEARNING STYLES - Hermino, Dr. Agustinus (IJRDO - Journal of Applied Management Science, 2016)
Education is the key word in any effort to improve the quality of humanlife within which it has a role and a purpose for 'humanizing', and process ofmaturation quality of life. Through the process is expected to be able to understandwhat is the meaning the essence of life, and for what and how to carry out the task ofliving and life correctly. That's why the focus of education is directed to theformation of a superior personality with emphasis on the quality of the maturationprocess of logic, heart, character, and faith. The highlight was reaching the point ofperfection education quality of life. The task of education also to motivate eachstudent to identify potential as early as possible, and schools provide services inaccordance with its potential and directs the preparation for the challenges ahead.Education leads to the formation of character, performance concrete and measurablethat develops in three domains capabilitie: cognitive, psychomotor, and affective.Multicultural means diversity of culture. The roots of multiculturalism is the culture,that viewed from its function as a guide for human life. In the context of nationbuilding, this multicultural term has formed an ideology in a wide range ofexperiences that shape popular perceptions of age, gender, religion, socioeconomicstatus, type of cultural identity, language, race, and disability. Organizational cultureat the school level requires the ability to mobilize the developments and changes thatdo creative activities, identify strategies, methods, means, or new concepts inteaching so that meaningful learning and delivery of quality education